Trabalho e fluxos migratórios: elementos da interculturalidade no contexto organizacional a partir da inserção de haitianos - Castro, Beatriz Leite Gustmann de (2018)
The present dissertation has as its main objective, to analyze elements of interculturality in the organizational context from the insertion of Haitian workers, in different organizations of Pato Branco - PR. For that, it was made a research which was exploratory, descriptive and with a qualitative approach. The sample of the study was composed by 11 interviewees who were bonded to organizations of diverse segments that hired Haitian workers. The first stage of data collection was carried out through official documents and reports available by agencies such as Ministry of Labor, Federal Police, Migration Observatory. Subsequently, interviews and focus group were conducted, using a semi-structured script with open questions. For the qualitative analysis of the data, the content analysis method was used (BARDIN, 2016). The categories of analysis defined in the first place were: Exchanges between different cultures; interaction between cultures, alterity, difference and identity. The results from the analytical categories show that in relation to the exchanges between cultures, the organizational environment is impermeable, that is, the national culture is predominant. Regarding the interaction between cultures, the results evidenced for the existence of a linguistic barrier reflecting in the work performance, segregation, as well as in the difficulty of interaction. Still, there is no mobilization to stimulate interaction that encourage the proximity between natives and migrants. In relation to alterity, the absence was verified, that is, there are no practices that contemplate the appreciation of the existing differences. The pay and technical skills gap also proved to be a barrier to growth and professional recognition. In the difference category, it was identified that communication is a challenge in intercultural management, because it is difficult to establish dialogues, due to lack of knowledge of the Portuguese language. The findings about identity reveal that institutional discourses prioritize democratic relations, to which all have equal opportunities and rights, however, these actions do not occur in practice. It is concluded that organizations need to invest in the preparation of teams that accommodate migrant workers, especially in terms of policies and communication practices, once it was noticed the distance caused by language limitations. It is necessary to improve the reading of the organizational scenario, as well as overcoming existing prejudices in organizational cultures and ethnocentric ways of perceiving the relationships between work and people. Thus, it is important to develop policies and strategies that enable actions for the effective integration of the migrant worker, and the promotion of cultural interaction.